The Morphology of Seed-Bearing Plants in The Qur’an: A Thematic Analysis of Tantawi Jawhari and Tafsir Ilmi by the IndonesianMinistry of Religious Affairs - Mulyawan, Andhiarizqi; Achmad, Yudianto; Lubis, Zakaria Husin; Kamaluddin, Ahmad (Jurnal Ilmu Pertanian Indonesia, 2025)
The Qur’an’s Natural Phenomena (Āyāt Kauniyyah) verses contain scientific clues, including one on seed-bearing plant morphology. The study aimed to explain Qur’anic references to seed-bearing plant morphology, as well as the interpretation of these verses in Tantawi Jauhari’s Tafsir Al-Jawâhir fî Tafsîr Al-Qur’ân Al-Karîm and Lajnah Pentashihan Mushaf Al-Qur’an’s Tafsir ’Ilmi Tumbuhan dalam Perspektif Al-Qur’an dan Sains. The qualitative approach used in this study was library research, with data gathered from a variety of relevant sources. The Qur’an is interpreted using the Al-Maudhu’i (thematic) methods. Both methods aimed to generate descriptive data by observing Qur’anic chapters and verses, as well as providing scientific insights into the subject. The Qur’an mentions seed-bearing plant morphology through physical descriptions and metaphors (amthāl) in 26 words throughout 39 chapters and 87 verses. The verses that provide complete interpretation of plant morphology in Tafsir Al-Jawâhir fî Tafsîr Al-Qur’ân Al-Karîm include Al An’am/6:99, which addresses floral morphology; An Naml/27:60, which examines roots, stems, and leaves; and Yasin/36: 80, which concentrates on the leaf. Meanwhile, in Tafsir ’Ilmi Tumbuhan dalam Perspektif Al-Qur’an dan Sains, Al An’am/6:99 is interpreted in terms of the "green substance" in plants, with a full description of the photosynthesis process related to At Takwir/81:17−18, Yasin/36:80, and Al Waqi’ah/56:71−72. Then, Al An’am/6:95 describes seeds as a component of plant development. Keywords: Al-Qur’an, plant morphology, scientific exegesis, seed-bearing plants, Tantawi Jauhari